How terrorist attacks distort public debates: a comparative study of right-wing and Islamist extremism - Teresa Völker (Journal of European Public Policy, 2024)
Previous research has shown how terrorist attacks attract media attention and influence public opinion and decision-makers. However, we lack a comparative assessment of the extent to which extremist ideologies matter and how they matter. Therefore, this paper compares mass media debates over extreme right and Islamist terrorist attacks. Theoretically, it innovates by linking research on discursive critical junctures and issue-specific discursive opportunity structures, emphasising the systematic differences between the two ideologies. Empirically, the study is based on an original, large-scale content analysis of mass media debates on all seven fatal attacks in Germany since 2015 (N0.167em=0.167em9047). It combines relational quantitative content analysis with frame and network analyses. The results show how ideologies behind terrorist attack shape political reactions and the framing of the key security threat. Notably, both types of attacks provide favourable conditions for the far right, and political elites play a central role in the diffusion of far-right frames. In contrast, victims and ethnic or religious minorities have little voice in public debates. Overall, the study contributes to a better understanding of the impact of terrorist attacks on Western democracies by emphasising the impact of ideology and distorted threat perceptions in public debates.
Keywords: 320; Far right; terrorism; public debates; right-wing extremism; Islamist extremism; public opinion